As expectativas dos profissionais com a prática do badminton para crianças autistas - Santos, Andriele Fabiane Pereira dos (My University, 2021)
The autistic spectrum gets manifested in childhood with impairments on social development, among others factors. Badminton is a dynamic sport practiced between two or four players. The implements of the game are a racket and a specific shuttlecock. Objective: To describe the main expectations that teachers have when starting a practice of badminton with autistic children. Methodology: Research adapting qualitative approach, with four professionals who work at Associação L'Aqua. An interview was applied from August to October 2020. Results: The following categories of analysis may be highlighted: The experiences of badminton, by professionals, might favor the application of the project: Empathy with the autistic; some aspects focused on the relationship between teacher and student; Development progress of the students; The methodological strategies; Expectations regarding the Autistic students who will participate in the project. Conclusion: It is concluded that the professionals who performed badminton with autistics students, have high expectations related to the improvement of motor and social skills of them. [resumo fornecido pelo autor]
O espectro autista se manifesta na infância com comprometimentos no desenvolvimento social, dentre outros fatores. Badminton é um esporte dinâmico praticado entre dois ou quatro jogadores. Como implementos de jogo, se usa raquete para rebater e lançar uma peteca, própria da modalidade. Objetivo: Descrever as principais expectativas que professores apresentam ao se iniciar uma prática do Badminton com as crianças com Autismo. Metodologia: Pesquisa numa abordagem qualitativa, com quatro profissionais que atuam na Associação L'Aqua. Uma entrevista foi aplicada no período de agosto a outubro de 2020. Resultados: Destacam-se as seguintes categorias de análise: As experiências ou vivências com o Badminton, por parte das profissionais, poderá favorecer a aplicação do projeto; A identificação com os Autistas; Alguns aspectos com foco na relação professor X aluno; Os avanços no desenvolvimento dos alunos; As estratégias metodológicas; As expectativas com relação ao aluno Autista que participará do projeto. Conclusão: Conclui-se que os profissionais que realizaram a prática do badminton com os autistas, têm grandes expectativas com a melhora no desenvolvimento motor e social desses alunos. [resumo fornecido pelo autor]
Keywords: Educação física; Professores de educação física; Autismo em crianças; Badminton